Water use efficiency in rubber tree seedlings subjected to water deficlit - Neto, Olinto Gomes da Rocha; Cano, Marco Antônio Oliva; Tiebaut, José Tracísio L. (Pesquisa Agropecuaria Brasileira, 2014)
Open pollinated seedlings from IAN 873 and IAN 717 rubber tree (Hevea spp.) clones grown in greenhouse were subjected to crescent water deficit by the water use efficiency and stomatal sensibility aiming an evaluation of primary productivity. Parameters such as stomatal resistance and transpiratory value were considered as drought avoidance. Water use efficiency, photosynthesis values, water compensation point and water saturation deficit were the parameters utilized in drought tolerance. The lowest values of water deficit saturation were observed in the IAN 873 progeny, suggesting, a lower tolerance to water stress when compared to IAN 717 progeny. A high water efficiency use was observed in the ratio net photosynthesis and transpiratory value in the IAN 717 progeny. On the other hand, when in lower relative content of water, the efficiency was higher when compared with IAN 873 progenies. Differences between both progenies were not stressed under limitant water conditions. In addition, progenies showed a higher prevention capacity than drought tolerance.